Evaluation of driving performance of two types of competitive wheelchairs for badminton made of two different metallic materials - Nonaka, M.; Kashiwazaki, H.; Ura, S.; Nagamori, M.; Uchiyama, H.; Shionoya, A. (Proceedings, 2020)
Currently, various types of wheelchairs for badminton have been developed for weight saving and functional improvement. The purpose of this study was to evaluate each performance of two types of competitive wheelchairs for badminton made of two different metallic materials. One of the wheelchairs used in this study was made of magnesium composite material, which was 45 GPs of Young`s modulus, 1.738 g/cm3 of the specific weight, and 9.57 kg of weight. Another was made of scandium-aluminum composite material, which was 70 GPa of Young`s modulus, 2.70 g/cm3 of the specific weight, and 10.81 kg of weight. The frames and weights of the wheelchairs were similar. In this experiment, the subject`s electromyograms from six muscles in driving each wheelchair were measured and analyzed. Furthermore, the motion in driving was captured and analyzed using a three-dimensional motion capture system. This experiment led to the following result: no significant difference was found in wheelchair performance due to the different materials.